Remote Monitoring System for Communication Base Based on Short Message - Xiao Rong Zhao; Fei Yue Ye; Xiu Fang Qian; Han Yu Fu; Wei Jin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents design and development of an automatic monitoring system of communication base which is an important means to realize modernization of mobile communication base station management. Firstly, this paper proposes the architecture of the monitoring system. The proposed system consists of mocrocontrollers, sensors, GSM module and MFRC500 etc. The value of parameters is measured in the system including terminal is studied and designed, including hardware design based on embedded system and software design. Finally, communication module is discussed. The monitoring system which is designed  based on GSM SMS(short message service) can improve the integrity, reliability, flexibility and intellectuality of monitoring system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3200